Chemical constituents of the roots of Kniphofia isoetifolia Hochst. and evaluation for antibacterial activity - Melaku Meshesha; Tsegaye Deyou; Abebe Tedla; Negera Abdissa (GarVal Editorial Ltda., 2017)
Context: The genus Kniphofia Moench, with species close to 70, is traditionally used to treat wide ranges of ailments including menstrual pains, infertility, abdominal cramps, wounds, malaria, chest complaint and hepatitis B. Kniphofia isoetifolia, an endemic species in Ethiopia, is known for wounds healing applications in Southern Ethiopia. Aims: To investigate the roots of Kniphofia isoetifolia and evaluate the extracts and its constituents for antibacterial activity. Methods: The roots of Kniphofia isoetifolia was extracted with chloroform/methanol (1:1 v/v), and the resulting crude extract was partitioned between EtOAc/H2O. The ethyl acetate extract afforded four compounds after chromatographic purification, and their identification was based on spectroscopic analyses. The extracts and pure compounds were evaluated for in vitro antibacterial activity on four bacterial strains namely Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa and Enterococcus faecalis. Results: The purification of the extract of roots of Kniphofia isoetifolia resulted in identification of four compounds (1 - 4). This is the first report on the phytochemical investigation of Kniphofia isoetifolia and occurrence of compound 1 in the genus Kniphofia. The extracts and isolates demonstrated antibacterial activity. The Compound 3 in some cases demonstrated comparable zone of inhibition with gentamycin. Conclusions: This is the first report of the occurrence of naphthoquinone derivative, 3,5,8-trihydroxy-2-methylnaphthalene-1,4-dione (1) in the genus Kniphofia which appears to have a chemotaxonomic significance to narrow down the gap between Alooideae and Asphodeloideae subfamily. The two dimeric anthraquinones (3, 4) showed strong activity with highest zone of inhibition recorded for asphodeline (3) against E. faecalis.